EXTENSIVE READINGCLASS: APPROACH AND READING MATERIALS FORCOLLEGE STUDENTS - RIA, GUSPA (Menara Ilmu, 2017)
This article discusses aboutextensive reading material for students in university level,the benefits of Extensive Reading for students, and Extensive Reading approach. It considersthe benefits extensive reading can bring to English language learners and teachers. Inclassroom, students read long texts or large quantities for general understanding, with theintention of enjoying the texts. In selecting reading material,teacher should pay attentiontoreading material, students’ choice, reading out of class, silent reading, language level, use ofdictionaries, and teacher as a model. Students are allowed to choose the books or article theyread depending on their interests in class. In this way students are encouraged to read forpleasure and should become better readers. It will also increase students’ reading fluency,motivation and vocabulary.Key words:extensive reading, benefit, approach, reading material, vocabulary